Coup D’état on South African Government: is state capture a threat to democracy? - Mulaudzi, K. M; Masenya, M. J. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
The purpose of this paper is to analyse instances of state capture and how it impacts on good governance and the society at large. In contemporary world so many things happen politically and suddenly to surprise the citizens. It is apparent that South Africa underneath the supervision of the current government is internally and externally tumbling apart. Investors are disinvesting, commodity prices are deteriorating, and the rand has slumped. Over the past years, the South African media houses as routinely published a series of alleged corrupt activities by senior state officials. Corruption has become increasingly institutionalised activity in State Owned Entities, thus, leading to the phenomenon of state capture. State capture is commonly understood as a state wherein individual(s) or groups that possess power to influence the public and private sector decisions to work to their personal advantage in the government. The emergence of debate, discussion and engagements pertaining to state capture and patronage networks in recent months has led to legislators, policymakers, academics and interested parties to scrutinise the potential effects that state capture could have on the South African government, its economy and the society at large. The paper concludes that only if a full commission of enquiry on those who alleged to be involved in the capturing of the state can be conducted and be prosecuted, then state capture will not happen in the future.
Journal article published in The 3rd Annual International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Corruption; Economy; South Africa; State Capture; Political corruption -- South Africa; Corruption